Inventarisasi Koleksi Anggrek (Orchidaceae) di Kebun Raya Purwodadi sebagai Sumber Informasi Kegiatan Kunjungan Studi - Elga Renjana; Risma Kris Hendrawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
Study visit is one of Purwodadi Botanic Garden services for students ranging from elementary to college. Orchids (Orchidaceae) is a collection of plants in Purwodadi Botanic Garden. The purpose of this study was to invent the orchid collections in Purwodadi Botanic Garden as a source of information for study visit activities. The inventory result showed that Purwodadi Botanic Garden had 670 orchid specimens consisting of 48 genera and 124 species. The most collected genus was Dendrobium consisting of 28 species. In the other hand, species with the largest number of specimens was Cymbidium finlaysonianum Lindl. Several collections were protected in Indonesia and included on the IUCN Redlist. Four species were selected as the learning object for study visit activities, i.e. Dendrobium anosmum Lindl., Paphiopedilum glaucophyllum J.J.Sm., Spathoglottis plicata Blume, and Vanda limbata Blume.